THE NEW SILK ROAD: THE EUROPEAN UNION, CHINA AND THE FUTURE OF TRADE - Kaplan, Zeynep (International Journal of Economic Practice and Policy, 2019)
Transport costs are one of the crucial factors that shape the world trade patterns. In order to promote transport facilitation and to create an environment for a more efficient flow of goods Chinese government launched the New Silk Road initiative in 2013. One major issue that has an impact on transport, and consequently on the future development of the initiative, is the growing trade flow between China and the European Union. An interesting fact, clearly indicated, about China is that the nation will become the world’s largest middle-class market in the next decades. The recent Chinese demographic transformation –the rise of middle class consumers- is expected to have critical dynamics for the relations between China and the European Union. With growing purchasing power and more European brand preferences, China’s middle income consumers are an obvious future target market for EU brands.